The relationship between law, ratified agreement and the EU law in the light of the Polish Constitution and application of the EU law by public administration in Poland - Woźniak, Marta (The Opole Studies in Administration and Law, 2017)
The article makes a presentation of the relation between legal acts belonging to the so-called foreign orders and the national law at the level of regulation contained in the Constitution of the Republic of Poland and the problem of application of the EU law by the Polish administrative authorities. The ratified international agreements and acts of the EU law are sources of administrative law and must be applied by the public authority of Member States. The article deals with two issues: the relationship between the international law and national law in the light of the Polish Constitution and application of the EU law by public administration in Poland. These issues can be dealt with separately but have a number of tangent points. The author does not aspire to present a comprehensive discussion of these issues, but intends to point out some aspects. It has been argued that the standard of application of international law by public administrations (which is also the accession treaties) and the EU law depends on how the constitution regulates the issue of international law relation to the domestic law. In Polish jurisdiction (the Constitutional Court and the Polish Supreme Administrative Court) the practice of respecting the principle of primacy of the EU law as well as the principle of a community of interpretation of this law has been established.